Factors affecting the quality of internal audit reports in Jordanian ministries and government institutions - Almalkawi, Malik Hussein Ahmad (Journal of Economic, Administrative and Legal Sciences, 2024)
This Study Aimed to Know the Factors that Leave an Impact on the Quality of Internal Audit Reports Issued by the Internal Control Unit and the Internal Audit Department in Ministries and Government Institutions in Jordan to Achieve the Purpose of this Study, the Descriptive Analytical Approach was Followed in order to Interpret the Phenomenon and Know the relationship between its elements. For the Purposes of Collecting Data, A Questionnaire was Prepared that Corresponds to the Objectives and topics of the Study. The Study Population Consisted of all Ministries and Government Institutions, and their Number Equaled (165), While the Sample Was Limited to (350) Workers in the Internal Control Departments in Ministries and Government Institutions at their Various Levels. The SPSS Statistical Program Package for the Purpose of Analyzing Data and Drawing Conclusions. The Results Showed that there is A Statistically Significant Relationship Between the Academic Qualification, Practical Experience, and Training of the Report Preparer and the Quality of Internal Audit Reports in Jordanian Ministries and Government Institutions, and the Existence of a Statistically Significant Relationship Between the Independence of the Internal audit Department, the Interest of Senior Management, Planning the Audit Process, and the Quality of Internal Audit Reports in Ministries and Institutions. The Jordanian Government, and therefore the Study Recommended the Need for Ministries and Government Institutions to Issue Bulletins or Booklets to Improve and Develop the Experience of the Internal Auditor.
Keywords: internal audit; quality of reports; Jordanian government institutions; Jordanian ministries